Asymptomatic people with well-controlled HIV do not have abnormal left ventricular global longitudinal strain - Hoy, Jennifer F.; Lee, Sue J.; Trevillyan, Janine M.; Dewar, Elizabeth M.; Roney, Janine; Dart, Anthony; Yang, Yan (Frontiers in Cardiovascular Medicine, 2023)
Background Previous studies have reported impairment in systolic and diastolic function in people with HIV (PWHIV). Our aim was to determine if echocardiographically measured left ventricular (LV) global longitudinal strain (GLS) is abnormal in asymptomatic PWHIV. Methods A cross-sectional study of PWHIV (n = 98, 89% male, median age 53 years) and HIV-negative people (n = 50, median age 53 years) without known cardiovascular disease were recruited from a single centre. All participants completed a health/lifestyle questionnaire, provided a fasting blood sample, and underwent a comprehensive echocardiogram for assessment of diastolic and systolic LV function, including measurement of GLS. Results All PWHIV were receiving antiretroviral therapy (ART) for a median of 12 years (IQR: 6.9, 22.4), the majority with good virological control (87% suppressed) and without immunological compromise (median CD4 598 cells/µl, IQR: 388, 841). Compared with controls of similar age and gender, there was no difference in GLS [mean GLS −20.3% (SD 2.5%) vs. −21.0% (SD 2.5%), p = 0.14] or left ventricular ejection fractions [65.3% (SD 6.3) vs. 64.8% (SD 4.8), p = 0.62]. Following adjustment for covariates (gender, heart rate, systolic and diastolic blood pressure, and fasting glucose), the difference in GLS remained non-significant. There were no differences in LV diastolic function between the groups. Exposure to at least one mitochondrially toxic ART drug (didanosine, stavudine, zidovudine, or zalcitabine) was not associated with impairment of LV systolic function. Conclusion No clinically significant impairment of myocardial systolic function, as measured by LV GLS, was detected in this predominantly Caucasian male population of PWHIV on long-term ART, with no history of cardiovascular disease.